The effect of subambient to elevated atmospheric CO2 concentration on vascular function in Helianthus annuus: implications for plant response to climate change. Issue 4 (3rd June 2013) - Rico, Christopher; Pittermann, Jarmila; Polley, H. Wayne; Aspinwall, Michael J.; Fay, Phillip A.
Summary: Plant gas exchange is regulated by stomata, which coordinate leaf‐level water loss with xylem transport. Stomatal opening responds to internal concentrations of CO2 in the leaf, but changing CO2 can also lead to changes in stomatal density that influence transpiration. Given that stomatal conductance increases under subambient concentrations of CO2 and, conversely, that plants lose less water at elevated concentrations, can downstream effects of atmospheric CO2 be observed in xylem tissue? We approached this problem by evaluating leaf stomatal density, xylem transport, xylem anatomy and resistance to cavitation in Helianthus annuus plants grown under three CO2 regimes ranging from pre‐industrial to elevated concentrations. Xylem transport, conduit size and stomatal density all increased at 290 ppm relative to ambient and elevated CO2 concentrations. The shoots of the 290‐ppm‐grown plants were most vulnerable to cavitation, whereas xylem cavitation resistance did not differ in 390‐ and 480‐ppm‐grown plants. Our data indicate that, even as an indirect driver of water loss, CO2 can affect xylem structure and water transport by coupling stomatal and xylem hydraulic functions during plant development. This plastic response has implications for plant water use under variable concentrations of CO2, as well as the evolution of efficient xylem transport.